Incidence of lymphomas in inflammatory bowel disease: report of an emblematic case, systematic review, and meta-analysis - Russo, Maria Francesca; Diddoro, Annalisa; Iodice, Alessandra; Severi, Carola; Castagneto-Gissey, Lidia; Casella, Giovanni (Frontiers in Medicine, 2023)
Introduction Over the past 20 years, the increasing use of combined therapy with immunosuppressants and biologic agents has markedly reduced the use of steroids in the management of inflammatory bowel diseases (IBD). However, medical therapy seems to promote, in the long run, carcinogenesis resulting in an increased risk of developing different types of malignancies, including lymphomas. The aim of this study was to systematically review the current incidence and prognosis of lymphoid neoplasms occurring in patients with IBD. Methods Studies analyzing the incidence of lymphomas in subjects of age >18 years affected by IBD were included in this systematic review and meta-analysis. Studies focusing on pediatric populations, not reporting person-years of follow-up, or with a duration < 1 year were excluded. PubMed, Embase, Web of Science Core Collection, and Cochrane Central Register were searched from inception through January 2022. Publication bias within studies was assessed using Begg's and Egger's tests and random effects model. Quantitative results were synthesized using relative-risk meta-analysis. PRISMA guidelines were used to carry out this systematic review (PROSPERO Registration Number: CRD42023398348). Results A total of 345 studies published between 1985 and 2022, with a total of 6,17,386 patients were included in the meta-analysis. Substantial heterogeneity between studies prevented the pooling of estimates (I2 = 97.19%). Evidence of publication bias was overall low (p = 0.1941). Patients affected by Crohn's disease (CD) were 1,86,074 (30.13%), while 2,78,876 (46.17%) were diagnosed with UC. The remaining 23.7% of cases were diagnosed with indeterminate colitis. Immunomodulators and biologic therapy were used in 24,520 (5.27%), and 17,972 (3.86%) patients, respectively. Reported incidence rates for lymphoma in IBD ranged from 0.0/100,000 person/years (py) (95% CI 0.0–3.7/100,000) to 89/100,000 py (95% CI 36–160/100,000). Reported incidence rates of lymphoma in CD ranged from 0.0/100,000 py (95% CI 0.0–3.7/100,000) to 91/100,000 py (95% CI 18–164/100,000). For UC, the incidence rate ranged from 0.0/100,000 py (95% CI 0.0–3.7/100,000) to 95/100,000 py (95% CI 0–226/100,000). Male-to-female ratio was ~4:1. Therapy with immunomodulators was directly associated with an increased incidence of lymphoma (p < 0.0001). Evidence of publication bias was overall low (p = 0 .1941). Conclusions The evidence arising from this study highlights a correlation between the use of immunomodulators and subsequent lymphoma development. Combined multidisciplinary approach and long-term follow-up are warranted in order to decrease mortality deriving from the coexistence of both conditions. Systematic review registration Identifier: CRD42023398348.